Effect of feeding enzyme mixture with Fibrolytic activity in dry and solubulized Forms on the performance of lambs - M.V.A.N. Suryanarayana; J. V. Ramana (Indian Journal of Veterinary and Animal Sciences Research, 2025)
One hundred lambs (11.8 kg ± 0.56) divided at random into 4 groups G1, G2, G3 and G4 were supplemented with exogenous fibrolytic enzyme mixture (EFE) in concentrates after 6 hours outside grazing. G1 and G2 were given 200 and 400 g of EFE per 50 kg feed in dry form, G3 and G4 were given EFE in solubulized form at 20 and 40 g per litre of water, respectively. The initial and final weights (kg) were non-significant among treatments. The total weight gain (kg) was higher (P